Population Aging and the Dynamics of Housing Demand: An Empirical Analysis Based on Population Age Structure - Li, Ping; Cheok Mui Yee (Asia Pacific Economic and Management Review, 2025)
The Dynamics of Population Aging and Housing Demand: An Empirical Analysis Based on Age Structure. Globally, population aging has emerged as an inescapable social phenomenon, particularly evident in China where this trend is even more pronounced. As the demographic structure continues to evolve, profound changes are taking place in the dynamics of housing market supply and demand, presenting both new challenges and opportunities for the development of the real estate market. By constructing theoretical models, this study explores the mechanisms through which changes in the age structure affect housing demand. Empirical analysis, supported by statistical data, reveals the specific transformations within the housing market under the backdrop of population aging. The findings indicate that not only does population aging directly reduce housing demand, but it also exerts far-reaching influences on the housing market indirectly through its impact on economic activities and policy orientations. This study aims to provide a scientific foundation for the formulation of relevant policies, thereby promoting the healthy development of the real estate market.